Corporate social performance : paradoxes, pitfalls, and pathways to the better world - Stachowicz-Stanusch, Agata (Contemporary perspectives in corporate social performance and policy (Series), 2015)
Corporatee Social Performance: Paradoxes- Pitfalls and Pathways to the Better World is authored by a range of international experts with a diversity of backgrounds and perspectives and provides a collection of ideas, examples and solutions on CSP implementation and problems that occur in this area of consideration.The last decade had abundant corporate, national and international ethical and financial scandals and crises. After this epoch of moral catastrophes stakeholders expect that corporations which are considered as the most powerful institutions today and which have enormous impact on our planet's ecosystems and social networks will take more active roles as citizens within society and in the fight against some of the most pressing problems in the world, such as poverty, environmental degradation, defending human rights, corruption, and pandemic diseases.Although Corporate Social Performance (CSP) has been a prominent concept in management literature and in the business world in recent years 'it remains a fact that many business leaders still only pay lip service to CSR, or are merely reacting to peer pressure by introducing it into their organizations.' (Bevan et al. 2004:4). So do really companies do 'well' by doing 'good' or maybe' companies engage in CSR in order to offset corporate social irresponsibility'? (Kotchen and Moony, 2012 p. 4). I hope that we would agree that companies and CSR only by working together guarantee their own survival and we- the society and the planet -will be much obliged (Thomé, 2009 p. 3).